Pelaksanaan Eksekusi Putusan Pengadilan Tata Usaha Negara Di Era Otonomi - Dezonda Rosiana Pattipawae (SASI, 2019)
The execution of the State Administrative Court Decision which has permanent legal force (inkracht van Gewijsde) in the era of autonomy is as wide as possible, and begins with the breakdown of the paradigm of regional autonomy in the 1945 Constitution of the Republic of Indonesia. Article 18, Article 18A and Article 18B, the implementation of regional government is based on the principles that become the normative basis. State Administrative Court decisions that cannot be executed have caused pessimism and apathy in society. The problem is that there is no executive power in the Law Number 5 of 1986 concerning the Regulation of State Administration. This condition is an alarming fact that the existence of a State Administrative Court Decision has not been able to bring justice to the public in the administrative sphere of government. The principle of the existence of a State Administrative Court Decision, to place judicial control in the implementation of good governance becomes biased in the Indonesian constitutional system.